Exploring the Factors Affecting Telemedicine Adoption by Integrating UTAUT2 and IS Success Model: A Hybrid SEM-ANN Approach - Thabet Z.; Albashtawi S.; Ansari H.; Al-Emran M.; Al-Sharafi M.A.; Alqudah A.A. (Institute of Electrical and Electronics Engineers Inc., 2025)
Telemedicine adoption has steadily grown due to its ability to provide accessible and cost-effective healthcare services. However, individuals' adoption rate still faces challenges, necessitating a comprehensive understanding of the factors influencing their adoption. This article explores the factors affecting telemedicine adoption by integrating Unified Theory of Acceptance and Use of Technology, the Information System success model, and perceived security. The integrated model is evaluated using a hybrid structural equation modeling-artificial neural network (ANN) technique based on data collected from 152 individuals. The results showed that performance expectancy, hedonic motivation, perceived security, and user satisfaction significantly drive telemedicine adoption. Additionally, user satisfaction is affected substantially by information quality, system quality, and service quality. However, effort expectancy, social influence, and facilitating conditions do not significantly impact telemedicine adoption. The ANN findings revealed that user satisfaction is the most important driver for telemedicine adoption, with a normalized importance of 100%. This article contributes to telemedicine literature by providing a comprehensive framework that combines two well-established theories, offering insights into the multifaceted factors affecting telemedicine adoption. The findings also provide practical implications for decision-makers, policymakers, telemedicine service providers, software companies, and developers, emphasizing the importance of addressing the identified factors to promote widespread telemedicine adoption and ensure its long-term success. ? 1988-2012 IEEE.